BODY COMPOSITION AND ITS ROLE IN DEVELOPMENT OF METABOLIC DISORDERS AND CARDIOVASCULAR DISEASES - O. M. Drapkina; L. V. Kupreyshvili; V. V. Fomin (Кардиоваскулярная терапия и профилактика)
There are many methods of the body composition assessment, but the most relevant are computed tomography and magnete-resonance tomography. Composition of the body shows the rate of fat amount and distribution in metabolic syndrome (MS) patients. It is known that MS increases the risk of atherosclerosis, arterial hypertension, type 2 diabetes, with further significant increase of cardiovascular morbidity and mortality. MS is associated with subclinical damage of internal organs; and the role of abdominal obesity is high. However, till recently there is no unified understanding of the role of visceral and subcutaneous fat.